to find the derivative of F(x) you use the Power Rule which is #d/dx (x^n) = nx^(n-1)# and the Constant Rule which is #d/dx (c) = 0#

#d/dx# just means to take the derivative in terms of x, #d/dx = F' = F'(x)#

Power Rule: #d/dx (x^n) = nx^(n-1)#

Constant Rule: #d/dx (c) = 0#

*(there are more derivative rules)*

#F(x) = 3x -5#

#d/dx F(x) = d/dx (3x-5)#

#F'(x) = 3x^(1-1) + 0#

*(5 becomes 0 because of the Constant Rule and 3x becomes 3 because of the Power Rule)

#F'(x) = 3#

now we are supposed to plug in #x = -3/4# into the derivative to get a y-value... but you can't because it's just a constant...

(Note: #d/dx# "means taking the derivative with respect to x" which means I want the derivative to contain x-variables. You might see #dx/dy or d/dy# which means to "take the derivative with respect to y", taking the derivative so that there are only y-variables...

For example, there might be an equation that looks like this:

#V = 2x + x^2# and they ask you to find #d/dx# so you just find the derivative and since all the variables are x you are good. Now, if they want you to find #d/dy# then they want to find the derivative and they want the all the x-variables to be y-variables. You won't have to worry about that later when you learn the Chain Rule.)